Phytohormone Abscisic Acid Improves Memory Impairment and Reduces Neuroinflammation in 5xFAD Mice by Upregulation of LanC-Like Protein 2 - Jeon, Seung Ho (Int J Mol Sci, 2020)
Alzheimer’s disease (AD), a type of dementia, is the most common neurodegenerative disease in the elderly. Neuroinflammation caused by deposition of amyloid β (Aβ) is one of the most important pathological causes in AD. The isoprenoid phytohormone abscisic acid (ABA) has recently been found in mammals and was shown to be an endogenous hormone, acting in stress conditions. Although ABA has been associated with anti-inflammatory effects and reduced cognitive impairment in several studies, the mechanisms of ABA in AD has not been ascertained clearly. To investigate the clearance of Aβ and anti-inflammatory effects of ABA, we used quantitative real-time polymerase chain reaction and immunoassay. ABA treatment inhibited Aβ deposition and neuroinflammation, thus resulting in improvement of memory impairment in 5xFAD mice. Interestingly, these effects were not associated with activation of peroxisome proliferator-activated receptor gamma, well known as a molecular target of ABA, but related with modulation of the LanC-like protein 2 (LANCL2), known as a receptor of ABA. Taken together, our results indicate that ABA reduced Aβ deposition, neuroinflammation, and memory impairment, which is the most characteristic pathology of AD, via the upregulation of LANCL2. These data suggest that ABA might be a candidate for therapeutics for AD treatment.